Extranodal marginal zone lymphoma of mucosa associated lymphoid tissue arising in the pleura - Malek, Anita; Lee, John Cho (Annals of Pathology and Laboratory Medicine, 2015)
A 77-year-old Haitian woman complained of two months history of cough and left upper quadrant abdominal pain. She had a remote history of tuberculosis that was treated back in Haiti many years ago. Imaging studies showed a left pleural effusion with posterior pleural thickening as well as lymphadenopathy in the left hilum and left supraclavicular area. The Pleural biopsy was consistent with extranodal marginal zone lymphoma of mucosa associated lymphoid tissue (EMZL/MALT). The supraclavicular lymph node also showed partial involvement by EMZL/MALT but was largely effaced by non-necrotizing granulomatous inflammation. Culture from this lymph node grew Mycobacterium tuberculosis complex. Primary pleural lymphoma is a rare entity and to the best of our knowledge only ten cases of pleural EMZL/MALT have been reported.We report a new case and a review of literature.Â 